Small Molecule Restores Itaconate Sensitivity in Salmonella enterica: A Potential New Approach to Treating Bacterial Infections. (30th June 2016) - Hammerer, Fabien; Chang, Justin H.; Duncan, Dustin; Castañeda Ruiz, Angel; Auclair, Karine
Abstract: In the context of increasing global antibiotic resistance, the need for alternative therapeutic targets is great. Although new antibiotics and resistance inhibitors provide temporary solutions, they are bound to become obsolete. In this work, we propose a new approach, coined "bacterio‐modulation" that aims to restore macrophage potency towards bacterial strains that are able to survive in phagolysosomes. One key defense in the macrophage's arsenal is itaconate, an endogenous molecule with antimicrobial activity. Some intracellular pathogens have evolved to produce itaconate‐degrading enzymes, which are required for intracellular proliferation and to promote pathogenicity. We herein present the first molecule able to resensitize Salmonella enterica to itaconate. Abstract : Become more sensitive : Although new antibiotics and resistance inhibitors provide temporary solutions to resistance, they are bound to become obsolete. In this work, we propose a new approach, coined bacterio‐modulation. It does not directly kill bacteria, and therefore minimally selects for resistant strains, but renders them more susceptible to macrophages' defenses.